Cheers to erosion - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Not all spin-offs are harmless. Take the case of blue agave (Agave tequilana) a plant from which Mexicans make the liquor Tequila which was introduced to control erosion in southern Africa 10 years ago. A company in the Graaff-Reinet area in...